2000
DOI: 10.1097/00019606-200006000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Mycobacterium tuberculosis in Tissues Showing Granulomatous Inflammation Without Demonstrable Acid-Fast Bacilli

Abstract: Early diagnosis of tuberculosis (TB) is important for early medical intervention and prevention of spread of the bacteria. It is not uncommon to observe granulomatous inflammation but without demonstrable acid-fast bacilli (AFB) on Ziehl-Neelsen (ZN) staining in tissues sent for histologic examination, and the definitive diagnosis of TB cannot be made because no concurrent tissue is sent for TB culture. In this study, the authors explored the feasibility of using polymerase chain reaction (PCR) for early detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
5
45
0
4
Order By: Relevance
“…Many prior studies have reported on the performance of PCR on various types of formalin-fixed, paraffin-embedded human tissues [11,[19][20][21]. In these reports, the sensitivity of the PCR ranged 66-100% and varied according to the method of PCR, target sequence and characteristics of the tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies have reported on the performance of PCR on various types of formalin-fixed, paraffin-embedded human tissues [11,[19][20][21]. In these reports, the sensitivity of the PCR ranged 66-100% and varied according to the method of PCR, target sequence and characteristics of the tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the use of PCR on human FFPE specimens for detection of MTC DNA with promising results, but almost all of them used in-house PCR methods. [15][16][17][18][19] The BDProbeTec ET Direct Detection assay (Becton Dickinson, Sparks, MD, USA) is commercially available for the detection of MTC in clinical specimens. This assay is based on simultaneous strand displacement amplification of MTC-specific IS6110 target DNA of 95 bp and real-time detection by fluorescentlabeled probes.…”
mentioning
confidence: 99%
“…Se han publicado diversos estudios en los que se reporta el uso de RPC en muestras de TFFP 26,[34][35][36][37] ; sin embargo, este es el primer estudio en el que se analiza una gran cantidad de muestras y en el que se incorpora una clasificacion del tipo de granuloma.…”
Section: Discussionunclassified